Aktivitas Komunikasi Pemasaran Jasa Bellshoes Loundry - Ardiyansyah, Ardiyansyah; Fahrizal, Fahrizal; Latief, Suryawahyuni; Afrizal, Afrizal (Universitas Batanghari Jambi, 2024)
Bellshoes Laundry implements marketing communication activities in selling its services as an effort to deal with any problems that arise. In this way, they can ensure that information about their services is conveyed well to customers and potential customers, and ensure that good relationships are maintained. This helps Bellshoes Laundry to remain competitive in the market and maintain customer satisfaction. The aim of the research is to determine marketing communication activities for Bellshoses Laundry services. The research was conducted using descriptive qualitative methods. In accordance with the problems studied, data collection was carried out using interview techniques, observation, documentation which were useful in providing facts and data regarding communication activities and their obstacles to being presented and analyzed. The research results show that the marketing communication activities carried out include advertising, packaging, merchandising and word of mouth activities.